TEACHING NATIONAL CULTURE AND VALUES THROUGH INTEGRATION OF FOLK ORAL ART IN AN INTERACTIVE AND DIGITAL EDUCATIONAL ENVIRONMENT. (Universal International Scientific Journal, 2026)
As is known, in modern higher pedagogical education, special attention is paid to the study of innovative and interactive methods of teaching folk oral art. Digital technologies, multimedia tools and interactive platforms allow transforming the pedagogical process, which leads students to develop creative thinking and a deep understanding of national culture and values.The study examines methods for integrating folk oral art into learning environments based on interactive storytelling, virtual and augmented reality (VR/AR), gamification, digital platforms and artificial intelligence. These approaches increase student engagement in the learning process, stimulate analytical and creative thinking, and serve to practically master cultural values.The results showed that the effective integration of folk oral art into interactive and digital learning environments modernizes the pedagogical process and develops students' creative competencies, which creates a foundation for the development of new innovative pedagogical strategies.
Keywords: : folk art, interactive education, digital learning environment, national culture, didactic innovations, creativity, VR/AR, gamification.